Sexuality in the New Testament : understanding the key texts - Loader, William R. G., 1944- (Louisville, Ky. : Westminster John Knox Press, 2010)
""Loader has brought together sources from the ancient world and opinions from a wide range of scholarship in many contentious areas concerning sexuality homosexuality, divorce, submission of women, sex outside marriage and celibacy in all of these he avoids leading the witness, letting the texts speak for themeselves He states the opinion of other scholars and occasionally of himself but his aim is to educate and not preach."--- David Instone-Brewer, Senior Research Fellow in Rabbinics and the New Testament, Tyndale House, Cambridge, UK" ""Loader brings an honest and authoritative voice to the discussion of what the New Testament says about human sexuality. He invites his readers to join in a serious engagement with the scriptural texts in their social and historical context, and in so doing he leaves them with the challenge of wrestling with how those texts should be read today"--- Judith Lieu, Lady Margaret's Professor of Divinity, University of Cambridge, UK" "Loader looks at hotly contested New Testament passages on sexuality and offers a fair and balanced treatment of what scholars say about them. He also offers an analysis of why interpreters say what they say and demonstrates how texts may be interpreted specifically to support a preformed opinion" "Written in straightforward nontechnical language this timely and informative text is ideal for college classes as well as Bible study groups."--BOOK JACKET.
Engaging the far and the near : where to begin -- 'With a man as with a woman' -- Model marriage and the household -- Adultery, attitude and disorder -- Divorce and remarriage -- Has sex a future? : the question of celibacy -- Conclusion : 'sex on the brain'? : love and hope.
Includes bibliographical references (p. 147-155) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Sex -- Biblical teaching